A construção social das expectativas de mães de crianças com paralisia cerebral grave frente à escolarização - Passos, Viviane Saladino (2007)
This research analyzed the ways in which families social levels determined the different trajectories in the search for solutions for their children with severe cases of cerebral palsy. These same social levels constituted maternal expectations relating to the process of their children s schooling. The main hypothesis relates to the factor of social levels, composed of economic, social and cultural factors, revealing themselves to be the fundamental elements, along with the degree of organic deficiency present in the child, which created seemingly similar parental expectations, but which in reality resulted in diametrically opposed significations. This study utilized the services provided by a private, philanthropic institution which treats and rehabilitates those with severe cerebral palsy. Two mothers, whose girls were in therapeutic processes at said institution, were selected as the subjects of this research. Thus, based on the fundamental works of Bourdieu, utilizing concepts and contributions from Goffman and Crochik, the analysis revolved around the conforming to a specific perspective not only of the possibilities and limitations of the deficiency but also of the most adequate social and educational spaces, arising in the first place from the necessity of the girl s mothers to deal with their children s severe disabilities. A qualitative study, semi directed interview methods were utilized with the two mothers, based on the methodological procedures indicated by Bourdieu. The interview results were analyzed via six thematic spokes, to whit: understanding the deficiency, socio-economic levels, discovery of the illness by the family, the search for formal treatment, past schooling experience and current academic level. The main discoveries refer to the unconscious forms in which different trajectories generate differentiated expectations about schooling and the social destinies of the women s daughters; especially, those trajectories which involved access to health services, specialized information, housing conditions and formal schooling contributed to the above mentioned expectations